Psychological Well-Being as a Socio-Psychological Factor in Choosing a Leader - Sargsyan, Hasmik; Asriyan, Elina; Zazyan, Khristine (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
This article presents the findings of a study examining the correlation between psychological well-being and the factors influencing the selection of a political leader. In contemporary society, where social, political, and economic conditions are in constant flux, psychological science—alongside other disciplines—has increasingly focused on the concept of well-being. This emphasis stems from the recognition that well-being constitutes a fundamental indicator of both individual and societal quality of life. The study was  conducted in two stages. The first stage involved a sample of 100 participants, while the second stage included 15 experts, comprising 8 psychologists and 7 political scientists. Statistical analysis of the data revealed a significant relationship between gender and psychological well-being indicators (χ² = 5.657; p < 0.05), as well as between age and psychological well-being indicators (χ² = 35.907; p < 0.05). Furthermore, Spearman’s correlation coefficient analysis indicated a statistically significant association between psychological well-being and the factors influencing the selection of a political leader (p < 0.05).The results of the expert survey suggest that individuals, guided by their specific needs, tend to prioritize and value leadership attributes that they perceive as instrumental in ensuring long-term satisfaction and well-being.
Keywords: Psychological well-being; person; leader; electoral behavior